Virtual reality in the rehabilitation of the balance in the elderly. - Oliveira, Juliana Alencar de; Guaratto, Thaís Feitosa; Bacha, Jéssica Maria Ribeiro; Evangelista, Roberta A. G. T.; Bocalini, Danilo Sales; Greve, Júlia Maria D’Andrea; Alonso, Angélica Castilho (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: Aging is characterized by a series of changes and adaptations that occur in the body progressively and irreversibly over the years. One of the consequences of senescence is the deficit of maintaining balance, this fact is explained by the involvement of the visual, somatosensory and vestibular systems. Given this scenario, the use of tools that can minimize these declines is of paramount importance. In recent times a resource that has been investigated is virtual reality, this technique stands out for presenting cognitive, motor and cardiorespiratory demands beneficial to the elderly. Objective: The present study aimed to perform a narrative review on the influence of virtual reality on the rehabilitation of balance in healthy elderly. Methods: A bibliographic survey was carried out in Portuguese and English, in the electronic databases: Pubmed, Lilacs, Pedro, Scielo, Scopus and Cochrone. A temporal limiter was applied from 2010 to 2015. Results: We selected 84 articles, however only five fit the criteria of the research. Despite the different methodologies and sample used, all articles selected showed significant improvement in postural balance after virtual reality therapy. However, a lack of standardization of the research protocols can be observed, making it difficult to reach a precise conclusion regarding the real effects of this technique for the study population. Conclusion: Virtual reality therapy was shown to be effective for the rehabilitation of postural balance in healthy elderly individuals. However, such evidence needs to be further investigated in future studies.